Performa Reproduksi Ikan Kerapu Cantang (Epinephelus fuscoguttatus x lanceolatus) Skala Hatchery - Affandi, Rangga Idris; Muahiddah, Nuri (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Grouper (Epinephelus sp.) is a superior Indonesian fishery commodity and has high economic value, has a high price and is an export commodity. Currently, grouper cultivation has developed, to meet the need for seeds, there is a need for a grouper hatchery business whose technology can be applied. Grouper seeds that are in demand, especially for the export market, are cantang grouper, which is a hybrid of female tiger grouper (Epinephelus fuscoguttatus) and male kertang grouper (Epinephelus lanceolatus). The aim of this research was to evaluate the reproductive performance and production performance of hybrid cantang grouper at the hatchery scale. The method used was active participation by directly following activities in the field and obtaining primary data (observation, interviews) and secondary data (literature study) at the Brackish Water Aquaculture Fisheries Center Situbondo, East Java. The stages of cantang grouper hatchery activities include container preparation, natural food culture, parent rearing, parent selection, parent spawning, egg handling, larva and fry care, water quality management, pest and disease control, as well as harvesting, packaging and transportation. The Hatching Rate (HR) value during the research obtained from stocking 150,000 eggs was 115,200 eggs or 76.8%. The Survival Rate (SR) value during the research obtained from stocking 115,200 fish with a total of 16,271 fish harvested or 14.1%.